Love Your Country: EEG Evidence of Actor Preferences of Audiences in Patriotic Movies - Zhu, Lian; Wu, Yufei (Frontiers in Psychology, 2021)
Movie watching is one of the common ways to spark love for the country. A good patriotic movie can arouse love and pride, encourage people to stand by their countries, and reinforce a sense of national belonging. To evoke audience emotion and enhance patriotism, the choice of actors is fundamental and a difficult dilemma for film producers. In this exploratory study, an electroencephalogram (EEG) with a rating task was used to investigate how actor types (i.e., skilled vs. publicity) in patriotic movies modulate audience's willingness to watch a film and their emotional responses. Behavioral results showed that audiences are more willing to watch patriotic movies starring skilled actors than publicity actors. Furthermore, brain results indicated that smaller P3 and LPP were elicited in response to skilled actors than publicity actors in patriotic movies. A larger theta oscillation was also observed with skilled actors than publicity actors. These findings demonstrate that the audience's willingness to watch a movie is deeply affected by actor types in patriotic films. Specifically, skilled actors engage audiences emotionally, more so than publicity actors, and increase the popularity of patriotic movies. This study is the first to employ neuroscientific technology to study movie casting, which advances film studies with careful scientific measurements and a possible new direction.